IMPLEMENTATION OF STATE TOURISM POLICY IN THE CONTEXT OF REGIONAL DEVELOPMENT - ZHURBA, Igor; NESTORISHEN, Ihor; MATYUKH, Serhiy (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article updates the issue of the need to improve the state tourism policy using tools of regional development and public-private partnership. The authors emphasized that the post-war recovery of Ukraine should involve the use of internal reserves and opportunities to restore Ukraine's economic potential, among which the tourism industry should occupy a leading place. It was emphasized that the field of tourism in Ukraine has significant unrealized potential, and under the condition of the development and implementation of an effective state tourism policy in combination with the use of regional development tools, the tourism industry can become a powerful basis for the economic recovery of both regions and the national economy as a whole.The purpose of the study is to analyze the current state of state tourism policy in Ukraine in the context of the use of regional development tools, as well as the specifics of the use of public-private partnership as a mechanism for implementing a new state policy in the field of tourism.The study stated that the transformations in the system of public administration and regulation, which were aimed at increasing the level of decentralization of public administration and the domestic economy, contribute to the use of public-private partnership tools in the field of tourism. The ultimate goal of decentralization was, first of all, to ensure the ability of local communities to independently, at the expense of their own resources, solve issues of local importance. It is about providing territorial communities with greater resources and mobilizing their internal reserves, namely: implemented changes have expanded the financial capabilities of local self-government and made it possible to make the new united communities economically self-sufficient and capable.Fiscal decentralization in combination with other modern instruments of state support creates conditions for a wide budget space for the implementation of local initiatives, and a key place in this system of relationships should be occupied by public-private partnership. The authors proposed the distribution of interests and areas of responsibility of the participants in the system of public-private partnership relations in the field of tourism.
Keywords: tourism; tourism policy; regional development; public-private partnership in the field of tourism; decentralization